2015
DOI: 10.2215/cjn.07100714
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells and Macrophages

Abstract: The mononuclear phagocytes (dendritic cells and macrophages) are closely related immune cells with central roles in anti-infectious defense and maintenance of organ integrity. The canonical function of dendritic cells is the activation of T cells, whereas macrophages remove apoptotic cells and microbes by phagocytosis. In the kidney, these cell types form an intricate system of mononuclear phagocytes that surveys against injury and infection and contributes to organ homeostasis and tissue repair but may also p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 121 publications
(118 reference statements)
2
55
0
1
Order By: Relevance
“…74 After acquiring antigens, dendritic cells process these to peptides, migrate to the secondary lymphoid organ, and present these antigenic peptides in the context of MHCs to T cells. Antigen-activated T cells proliferate and produce clones specific for the antigen.…”
Section: Antigens and Dendritic Cellsmentioning
confidence: 99%
“…74 After acquiring antigens, dendritic cells process these to peptides, migrate to the secondary lymphoid organ, and present these antigenic peptides in the context of MHCs to T cells. Antigen-activated T cells proliferate and produce clones specific for the antigen.…”
Section: Antigens and Dendritic Cellsmentioning
confidence: 99%
“…The renal tubular cell itself may have immunologic properties when appropriately activated, including phagocytosis and subsequent antigen presentation, 61 as well as co-stimulation of dendritic cells 62,63 or lymphocytes. 64 The proximal tubular cell is activated to migrate and proliferate in order to replenish the tubular structure, but it also produces chemoattractants and fibrogenic factors (reviewed in 65,66 ).…”
Section: The Pathophysiology Of Progressive Ckdmentioning
confidence: 99%
“…How to distinguish between renal macrophages or dendritic cells is an area of controversy. Although the presence of CD11c + cells negative for expression of the macrophage markers F4/80 suggests the presence of myeloid DCs [37, 38], F4/80 is now recognized to also be expressed on renal resident CD11c + DCs [39, 40]. However, a substantial number of studies have demonstrated that the CD11c + /F4/80 - and CD11c + /F4/80 + subsets have distinct effects on recovery and regeneration following IRI.…”
Section: Discussionmentioning
confidence: 99%